2020
DOI: 10.1108/jhom-10-2019-0295
|View full text |Cite
|
Sign up to set email alerts
|

Managerial workarounds in three European DRG systems

Abstract: PurposeAttempts to transform health systems have in many countries involved starting to pay healthcare providers through a DRG system, but that has involved managerial workarounds. Managerial workarounds have seldom been analysed. This paper does so by extending and modifying existing knowledge of the causes and character of clinical and IT workarounds, to produce a conceptualisation of the managerial workaround. It further develops and revises this conceptualisation by comparing the practical management, at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…It is reported that DRGs can help shorten hospital stay ( 35 ), reduce operations requiring expensive surgical instruments ( 36 ), and reduce medical costs ( 37 ). Although a lot of basic work needs to be carried out to realize DRG, including establishing adequate infrastructure, improving human resource capacity and improving the information management system ( 38 , 39 ), these works are of great value, because scientific evaluation of medical service performance helps to improve clinical practice. At present, the DRGs tool has been widely concerned and applied to several clinical professional medical service evaluation ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that DRGs can help shorten hospital stay ( 35 ), reduce operations requiring expensive surgical instruments ( 36 ), and reduce medical costs ( 37 ). Although a lot of basic work needs to be carried out to realize DRG, including establishing adequate infrastructure, improving human resource capacity and improving the information management system ( 38 , 39 ), these works are of great value, because scientific evaluation of medical service performance helps to improve clinical practice. At present, the DRGs tool has been widely concerned and applied to several clinical professional medical service evaluation ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in our study, the rate of early discharge (within 72 h) increased annually, with only a slight reduction in the early discharge rate in the first part of 2020, which may be attributed to new organizational issues that arose during the COVID-19 pandemic, increasing the difficulty for readmission due to the need for repeated SARS-CoV-2 testing and the presence of specific emergency room pathways for patients with fever 22 . The Italian healthcare system may also have hindered the shift towards early discharge (72 h) owing to the diagnostic related group (DRG) system regulations related to reimbursement for different procedures managed on a regional basis 23 , 24 . Considering all these issues, the modifiable factors that could be evaluated regarding the anticipation of discharge are surgeons’ perceptions and patients’ expectations in terms of comfort at the time of discharge, as well as fear of encountering management issues if an outpatient complication occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, scholars have focused on the influence of various factors, such as government intervention (21,22), medical service quality (17,(23)(24)(25), and payment mode of medical services (26,27), on the results of pricing games (2,(28)(29)(30). Behzad and Jacobson (31) investigate the impact of government price intervention and duopoly competition on medical price-setting.…”
Section: Related Workmentioning
confidence: 99%